Marvelous Mattie : how Margaret E. Knight became an inventor - McCully, Emily Arnold (Farrar, Straus, Giroux, 2006)
Mattie Knight loved to make things ranging from a foot warmer for her mother or toys for her older brothers. Or, when she was 12, a metal guard to prevent shuttles from shooting off looms and hurting workers. Later, Mattie invented a machine that could cut and glue the square-bottomed paper bags we still use today. Meet the woman known as "the Lady Edison."